2000
DOI: 10.1007/s002130000385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of central 5-hydroxytryptamine depletion on inter-temporal choice: a quantitative analysis

Abstract: According to the multiplicative hyperbolic model, parallel displacement of the linear indifference function uniquely specifies a change in time discounting. Thus these results indicate that central 5-HT depletion results in an increase in the rate of time discounting for food reinforcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 32 publications
(40 reference statements)
2
73
0
1
Order By: Relevance
“…Mobini et al (2000a, b) found that while global serotonergic depletions altered delay discounting (as one might expect), it did not alter probabilistic discounting, suggesting that serotonin may only influence responses to risk where choice of the less likely options can be reinforced with larger rewards (Mobini et al, 2000a). Long et al (2009) tested for the effects of tryptophan depletion using a tightly controlled paradigm in which macaques were given choices between safe behavioral options and risky behavioral options that carried variable pay-offs (Long et al, 2009).…”
Section: Serotonin and Risky Choicementioning
confidence: 92%
See 1 more Smart Citation
“…Mobini et al (2000a, b) found that while global serotonergic depletions altered delay discounting (as one might expect), it did not alter probabilistic discounting, suggesting that serotonin may only influence responses to risk where choice of the less likely options can be reinforced with larger rewards (Mobini et al, 2000a). Long et al (2009) tested for the effects of tryptophan depletion using a tightly controlled paradigm in which macaques were given choices between safe behavioral options and risky behavioral options that carried variable pay-offs (Long et al, 2009).…”
Section: Serotonin and Risky Choicementioning
confidence: 92%
“…In rats, global depletions of serotonin have been shown to increase the value of a hyperbolic discounting parameter for the value of future rewards (Mobini et al, 2000a;Wogar et al, 1993). In humans, (Tanaka et al (2004) have articulated a model in which serotonin is proposed to modulate reinforcement value signals across different time scales within the ventral striatum and the dorsal striatum, respectively.…”
Section: Computational Models Of Serotoninmentioning
confidence: 99%
“…Decision-making behavior impinges on cortical/striatal pathways, accounting for processing of incentive values when choosing between two alternatives (Montague and Berns, 2002;Glimcher and Rustichini, 2004;Schultz, 2004). We gave animals a choice between a smaller certain reinforcer and a larger but probabilistic one, a protocol also used to measure impulsivity (Mobini et al, 2000;Evenden, 1999). Economical considerations play, however, a major role in such a protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Central 5-HT manipulations are reported to affect the ability to wait for reinforcement in studies performed with paradigms for either impulsive-choice (e.g. [8,38]) or impulsive-action (e.g. [13,15]).…”
Section: Cognitive Impulsivitymentioning
confidence: 99%
“…[13,15]). For example, lesions of 5-HT pathways [8,15,38] as well as PCPA administration [8,13] resulted in increased impulsivity. Moreover, SERT −/− rats showed increased correct response latency and decreased premature responding in the 5-choice serial reaction time task (5-CSRTT; [24]).…”
Section: Cognitive Impulsivitymentioning
confidence: 99%